Bacteriological Analysis of Drinking Water from urban and Peri-Urban Areas of Peshawar - Sarwar, Ghulam; Khan, Jafar; Iqbal, Rashid; Afridi, Akbar Khan; Khan, Abbas; Sarwar, Rubina (Journal of Postgraduate Medical Institute, 2011)
To determine bacterial loads and contaminants in drinking water in and around Peshawar as to form water quality guidelines for judgement of the acceptability of public drinking water supplies. A total of 224 water samples inan around peshawar were assessed fro bacteriological contamination. it is desireable to disinfect all supplies of drinking water before distribution and consumption in view of its great public health signifcance.